Compensatory Growth in Pinus ponderosa (Dougl Ex Laws) Plantations Under Early Silvicultural Treatments - Letourneau, Federico Jorge; Medina, Andrea Alejandra; Ancalao, Marcos; Saihueque, Matías Horacio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Early pruning and thinning in Pinus ponderosa, plantations in Andean Patagonia triggered compensatory growth, characterized by greater trunk growth and structural adjustments. We used a factorial design and mixed-effects models to evaluate stem growth, crown light dynamics, tracheid length (TL), foliar biomass (FB), wood density (WD), and Huber values (Hv) five years after treatment. Trees under combined pruning and thinning (PT) showed the greatest basal area increment, indicating resource reallocation to supportive structures despite early foliage loss. Pruned trees maintained higher Hv and achieved partial recovery of FB. Tracheid elongation was greatest in treated trees, suggesting accelerated xylem maturation, while WD remained unchanged. These results demonstrate the structural plasticity of P. ponderosa, which maintains hydraulic function and growth after canopy disturbance. Our findings provide useful guidance for silvicultural planning in temperate plantations. Highlights: Early pruning and thinning triggered compensatory stem growth through hydraulic and structural adjustments, guiding adaptive management in Andean Pinus ponderosa plantations. The Huber value (Hv) captured the balance between conductive tissue and leaf biomass, revealing hydraulic rebalancing after canopy modification in young plantations. Tracheid elongation indicated accelerated xylem maturation in treated trees without affecting wood density. Findings highlight the potential of early canopy interventions to enhance productivity and hydraulic resilience in managed temperate conifer plantations.